Non-contrast spiral computed tomography diagnosis of urolithiasis and associated features: hospital based study - Dahiphale, Devidas; Apte, Abhang; Dahiphale, Anjali Pawar (International Journal of Research in Medical Sciences, 2016)
Background: Urolithiasis is prevalent across the world and affects a diverse group of people, irrespective of culture, race or geographic location. Non-contrast computed tomography (CT), has been considered as gold standard for the initial as well as follow-up assessment of patients with suspected urolithiasis. Present study describes the findings on non-contrast spiral computed tomography in clinically suspected patients of urolithiasis visiting radiodiagnosis department of a tertiary care hospital. Methods: It is a descriptive observational study done at Department of Radiodiagnosis and Imaging at Shri Chhatrapati Shivaji Maharaj General Hospital in Solapur district of Maharashtra state in India. Study duration was Jan 2005 to Oct 2006. 120 patients who presented with symptoms and signs of urolithiasis for diagnosis and treatment in Department of Surgery and Medicine, including the referrals from other hospitals and institutes and referred to Department of Radiodiagnosis and Imaging of the institute for computerised tomography (CT) were enrolled. Detailed history and physical examination was done. The description of findings on non-contrast spiral CT study was done with respect to size and CT attenuation value of the calculus, secondary signs of obstruction, CT diagnosis of urolithiasis, genitourinary or other diseases. Results: In hundred patients diagnosed as urolithiasis on NCSCT, 140 calculi were found. The mean calculus size (breadth) was 4.65 mm ± 7.03 with a range of 1 to 70 mm. The mean calculus size (length) was 11.1±12.87 mm with a range of 2 to 110 mm. The range of CT attenuation value of calculus was from 60 to 1100 with median value of 311 HU. Among the 100 patients of urolithiasis, hydronephrosis (84%) and hydroureter (82%) were the most common secondary signs of obstruction. Out of 120 patients suspected clinically with diagnosis of urolithiasis, 99 (82.5%) had obstruction with or without urolithiasis. In 86 (71.7%) patients, obstruction with urolithiasis was present. In 13(10.8%) patients, obstruction because of cause other than urolithiasis was present. We have observed additional diagnosis related to genito-urinary tract in 16 (13.5%) cases. We have observed additional diagnosis not related to genito-urinary tract in 6 (0.5%) cases. Conclusions: Non contrast spiral CT scan evaluation helped in diagnosis of urolithiasis and secondary obstruction. It also provided very useful information regarding genitourinary as well as other than genitourinary pathology.